The role of cardiac energy metabolism and during stress in hypertrophic and dilated cardiomyopathy. - Dass, S (2012)
Both hypertrophic (HCM) and dilated cardiomyopathy (DCM), though differing in their aetiologies, share features of impaired resting energetics. The aim of this thesis was to determine if cardiac high energy phosphate metabolism, measured as the phosphocreatine (PCr)/ATP ratio using 31Phosphorus magnetic resonance spectroscopy (31P MRS), is further impaired during exercise in these pathologies. This would provide a possible explanation for the high incidence of exercise related death in HCM and DCM as well as the blunted inotropic response to exercise in DCM. Furthermore, this thesis investigates the role of stress perfusion and stress tissue oxygenation in HCM (as these are hypothesized to exacerbate the primary defect in energetics) and exercise training in DCM (which is hypothesized to improve function though the mechanisms are uncertain). This work developed a novel protocol for measuring 31P MRS in a clinically acceptable time frame. The traditional acquisition is at least 20 minutes (as much as 40 minutes in subjects with lower pulse rates). This is a particularly long time to allow for exercise in the magnet particularly in the symptomatic DCM cohort. Hence this work meticulously developed a shorter 8 minute protocol. Its validity, reproducibility and application to exercise were confirmed. The post processing of the MRS data was further improved for calculating blood contamination and tested with both simulated and patient data, including normal, hypertrophied and thinned myocardium. Applying this new method, this thesis is the first to report a further decrease in exercise energetics in HCM. The relationship between perfusion, tissue de-oxygenation and energetic compromise during exercise was then explored in HCM. Athletes, with physiological hypertrophy, were used as an additional control group in these experiments. These results demonstrated a strikingly blunted oxygenation response of the HCM heart to stress even in the pre-hypertrophy HCM mutation carriers. However, as a group, the data did not show a correlation between the blunted oxygenation response and the percentage change in PCr/ATP during exercise. None-the-less, these results can potentially be useful for distinguishing between hypertrophy in the athletes and pathological hypertrophy in HCM and for distinguishing HCM mutation carriers’ pre hypertrophy and the normal heart. In the DCM cohort, this thesis explored the impact of exercise training on cardiac metabolism and function. The results showed no change in cardiac energetics and left ventricular ejection fraction during 8 minutes of exercise. In addition, an eight week home exercise programme did not alter resting or exercise cardiac PCr/ATP, but improved cardiac function during rest and exercise, and increased exercise tolerance and quality of life scores. In conclusion, this thesis reports further insights into cardiac exercise energetics in HCM and DCM and its relationship to perfusion and oxygenation in HCM and to exercise training in DCM. Therapies that decrease the energy cost of cardiac work during exercise may prove beneficial targets to explore further in these conditions.